Low-loss temperature-stable olivine-type microwave dielectric ceramic and preparation method thereof
Ga3+ and Al3+ ions replace Mg2+ and Si4+ positions, and CaTiO3 is added to form a single-phase solid solution of Mg2-xGaxSi1-xAlxO4, which solves the problems of poor temperature stability and high dielectric loss of existing Mg2SiO4 ceramics, and realizes the preparation of low-loss and temperature-stable microwave dielectric ceramics, which are suitable for 5G/6G millimeter wave communication applications.
Patent Information
- Application Number
- CN202310608847.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-05-29
AI Technical Summary
The existing Mg2SiO4 peridot microwave dielectric ceramics have poor temperature stability, high dielectric loss and high sintering temperature, which limit their use in 5G/6G millimeter wave communication applications.
By replacing the Mg2+ and Si4+ positions with a small number of Ga3+ and Al3+ ions, a single-phase solid solution of Mg2-xGaxSi1-xAlxO4 is formed, the lattice vibration is reduced, and CaTiO3 is added to adjust the resonant frequency temperature coefficient to form a low-loss, temperature-stable microwave dielectric ceramic.
Microwave dielectric ceramics with a dielectric constant of 8.32~9.52, Q×f is 39000GHz~94500GHz, and a resonant frequency temperature coefficient of -16.96~12.59ppm/℃ are achieved. They have low dielectric constant, low loss and good temperature stability, and are suitable as candidate materials for millimeter wave applications.
Smart Images

Figure CN116589270B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microwave dielectric ceramics, and in particular relates to a low-loss temperature-stable olivine-type microwave dielectric ceramic and a preparation method thereof. Background Art
[0002] The high frequency and large bandwidth of 5G / 6G millimeter waves make the devices more susceptible to temperature drift, so the materials are required to have better quality factors and temperature stability. Low dielectric constant microwave ceramic materials have the characteristics of fast signal transmission response and low dielectric loss at high frequencies. They are suitable for microwave / millimeter wave high-frequency communication applications, especially as key components of mobile communication base station RF units such as dielectric resonators, dielectric filters, and substrates.
[0003] Forsterite is a commonly used microwave dielectric ceramic with a low dielectric constant. Its chemical formula is Mg2SiO4 and it has an orthorhombic structure. Due to its low dielectric constant and dielectric loss, it changes little with frequency, and its raw materials are widely available and inexpensive. It is non-toxic and harmless, and its synthesis method is simple. It is often used as a substrate material for electronic circuits. However, there are a series of problems in the preparation process of forsterite (Mg2SiO4) ceramics: (1) poor temperature stability; (2) high sintering temperature, and the densification temperature is often higher than 1450℃; (3) the production of the second phase MgSiO3, which leads to increased dielectric loss, wider passband, and poor circuit selectivity; which seriously limits its application range. If the material with a positive resonant frequency temperature coefficient is directly used for composite adjustment, its dielectric loss will be further increased, thus affecting its practical application. In summary, the key to meeting the application of millimeter wave communication dielectric devices such as 5G / 6G is to ensure its low loss while reducing the sintering temperature and adjusting the resonant frequency temperature coefficient to near zero. Summary of the invention
[0004] The problem to be solved by the present invention is to overcome the problems of poor temperature stability, dielectric loss and high sintering temperature of Mg2SiO4 olivine microwave dielectric ceramics in the prior art, and to provide a new component formula and preparation method of forsterite type microwave dielectric ceramics.
[0005] Mg of the present invention 2-x Ga x Si 1-x Al x O4 is formed by a small amount of Ga 3+ , Al 3+ Ion substitution Mg 2+ and Si 4+ The formation of a single-phase solid solution changes the crystal structure of microwave dielectric ceramics, reduces lattice vibration, reduces the intrinsic loss of forsterite-based ceramics, and forms ultra-low loss microwave dielectric ceramics. On the other hand, by using a positive temperature coefficient of CaTiO3 and Mg1.99 Ga 0.01 Si 0.99 Al 0.01 O4 forms a temperature-stable composite material.
[0006] The present invention provides a low-loss temperature-stable olivine-type microwave dielectric ceramic, wherein the chemical formula of the low-loss temperature-stable olivine-type microwave dielectric ceramic is (1-y)Mg 2-x Ga x Si 1-x Al x O4-yCaTiO3, where the subscript x ranges from 0<x≤0.02, Mg 2-x Ga x Si 1-x Al x The mass ratio of O4 to CaTiO3 is (1-y):y; the range of y is 9%≤y≤13%.
[0007] The microwave dielectric ceramic is composed of the phase Mg 2-x Ga x Si 1-x Al x The invention discloses an olivine composite ceramic composed of O4 and CaTiO3. The low-loss temperature-stable olivine microwave dielectric ceramic has a dielectric constant of 8.32 to 9.52, a Q×f of 39000 GHz to 94500 GHz, and a resonant frequency temperature coefficient of -16.96 to 12.59 ppm / °C.
[0008] The present invention also provides a method for preparing low-loss temperature-stable olivine-type microwave dielectric ceramics.
[0009] First, prepare Mg 2-x Ga x Si 1-x Al x O4, where 0<x≤0.02;
[0010] To the prepared Mg 2-x Ga x Si 1-x Al x CaTiO3 is added to O4, among which Mg 2-x Ga x Si 1-x Al x The mass ratio of O4 to CaTiO3 is (1-y):y; the range of y is 9%≤y≤13%.
[0011] The present invention also provides a method for preparing a low-loss temperature-stable olivine-type microwave dielectric ceramic, comprising the following steps:
[0012] (1) Obtaining raw materials MgO, Ga2O3, Al2O3, SiO2, CaTiO 3, Purifying the raw materials MgO, Ga2O3, Al2O3, SiO2 and CaTiO3;
[0013] (2) weighing raw materials according to the molar ratio of Mg:Ga:Si:Al of 2-x:x:1-x:x, mixing and placing in a ball mill filled with ZrO2 balls, adding 4 / 5 of anhydrous ethanol to the ball mill for a first ball milling to obtain a powder after a first ball milling; wherein the range of x is 0<x≤0.02;
[0014] (3) drying, grinding, sieving, and then pre-calcining the powder after the first ball milling;
[0015] (4) Grind the pre-burned powder and then press Mg 2-x Ga x Si 1-x Al x The mass ratio of O4 to CaTiO3 is (1-y):y; CaTiO3 is added, the mixture is placed in a ball mill, ZrO2 balls and anhydrous ethanol are added, and secondary ball milling is performed to obtain a powder after secondary ball milling; wherein the range of y is: 9%≤y≤13%; (5) the powder after secondary ball milling is dried, and then the powder is screened for the first time, granulated, screened for the second time, pressed into tablets, and finally sintered to obtain the microwave dielectric ceramic.
[0016] Preferably, the specific steps of the purification treatment in step (1) are: calcining the MgO at 900°C for 2 hours to decompose the basic magnesium carbonate Mg(OH)2CO3 formed due to water absorption; and drying the Ga2O3, Al2O3, SiO2 and CaTiO3 at 80°C for 24 hours to remove moisture.
[0017] Preferably, the specific conditions of the first ball milling in step (2) are: a rotation speed of 220 r / min and a time of 12-24 h.
[0018] Preferably, in step (3), the drying temperature is 80°C, the drying time is 24 hours, the sieving uses a 100-mesh standard sieve, the pre-burning condition is 1150°C, the heating rate is 4°C / min, the temperature is kept at 1150°C for 4 hours and then cooled to room temperature with the furnace.
[0019] Preferably, the specific conditions for the secondary ball milling in step (4) are: a rotation speed of 220 r / min and a time of 12-24 h.
[0020] Preferably, in the step (5), the drying condition is 80° C. for 24 to 36 hours, the first sieving uses a 100-mesh standard sieve, and then polyvinyl alcohol (PVA) with a powder mass of 10 wt% and a concentration of 10 wt% is added as a binder for granulation, and the second sieving uses a 60-mesh standard sieve; the tabletting uses 0.9 g to 1.1 g of powder in a steel mold with a diameter of 12 mm, and is pressed into a cylindrical blank with a height of 4 to 6 mm and a diameter of 12 mm under a pressure of 150 MPa.
[0021] Preferably, in step (5), the sintering comprises: firstly heating to 650°C at a rate of 2°C / min for debinding for 3 hours, then heating to 1250-1400°C at a rate of 4°C / min for sintering for 3 hours, and finally cooling to 800°C at a rate of 2°C / min and then cooling to room temperature with the furnace.
[0022] The present invention uses trace amount of Ga 3+ and Al 3+ Replace part of Mg in Mg2SiO4 2+ and Si 4+ position, reducing lattice vibration, thereby reducing the intrinsic loss of the material, and obtaining Mg 2-x Ga x Si 1-x Al x O4 ceramics have a dielectric constant of 6.55 to 7.05, a Q×f of 203700 GHz to 236600 GHz, and a resonant frequency temperature coefficient of -54 to -38 ppm / ℃, which has both a low dielectric constant and an ultra-high quality factor. 2-x Ga x Si 1-x Al x O4 is added to CaTiO3 to adjust the resonant frequency temperature coefficient and reduce the sintering temperature. Its dielectric constant is 8.32-9.52, Q×f is 39,000GHz-94500GHz, and the resonant frequency temperature coefficient is -16.96-12.59ppm / ℃. This material has low dielectric constant, low loss and good temperature stability, and is expected to become a candidate material for millimeter wave applications.
[0023] The patent with publication number CN106032318A discloses a low temperature co-fired ceramic material and a preparation method, characterized in that the chemical formula is xR2O-yR'O-zM2O3-wM'O2, wherein R is at least one of Li, Na, and K, R' is at least one of Mg, Ca, Sr, Ba, Zn, and Cu, M is at least one of B, Al, Ga, In, Bi, Nd, Sm, and La, and M' is at least one of Si, Ge, Sn, Ti, and Zr. x, y, z, and w are mass percentages, and x ≥ 0, y ≥ 0, z ≥ 20%, w ≥ 15%, and x + y + z + w = 0. A LTCC microwave dielectric material having a dielectric constant of less than 6 and a Q×f value of less than 35100 GHz is obtained by reacting raw materials that can form microcrystalline glass through multiple steps at a temperature below 950°C. This microwave dielectric material has a large dielectric loss and poor microwave performance. The (1-y)Mg 1.99 Ga 0.01 Si 0.99 Al 0.01 O4-yCaTiO3 (0<x≤0.02, 8wt%≤y≤13wt%) is essentially different from the above-mentioned low-temperature co-fired powder xR2O-yR'O-zM2O3-wM'O2, and cannot be simply considered to be a multi-component composite crystalline phase compound generated by the mixed reaction of oxides. This is because the Mg 2-x Ga x Si 1-x Al x O4 is formed by a small amount of Ga 3+ , Al 3+ Ion substitution Mg 2+ and Si 4+ The formation of a single-phase solid solution and the use of materials with positive temperature coefficients to adjust the resonant frequency temperature coefficient are fundamentally different from the above-mentioned low-temperature co-fired powder in terms of their impact on the performance of microwave ceramics. The above-mentioned low-temperature co-fired powder xR2O-yR'O-zM2O3-wM'O2 is made from raw materials that can form microcrystalline glass, and a multi-composite crystalline phase ceramic raw material is synthesized through a multi-step solid-phase reaction to reduce the sintering temperature. Although the same elements are contained, the highest quality factor only reaches 35100GHz, which does not meet the ultra-low loss requirements. The present invention forms a single-phase solid solution by replacing a small amount of ions, changes the crystal structure of microwave dielectric ceramics, reduces lattice vibrations, reduces the intrinsic loss of forsterite-based ceramics, and forms ultra-low loss microwave dielectric ceramics. On the other hand, by using CaTiO3 and Mg with a positive temperature coefficient 1.99 Ga 0.01 Si 0.99 Al 0.01 Therefore, the above xR2O-yR'O-zM2O3-wM'O2 results have no reference value for the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Mg in Comparative Examples 1 to 3 and Examples 1 to 4 2-x Ga x Si 1-x Al x Q×f value variation trend of O4 at the optimal sintering temperature; obviously Ga 3+ 、Al 3+ Cooperative substitution occupies part of the Mg in the Mg2SiO4 lattice 2+ and Si 4+ When 0≤x≤0.02mol, an ultra-low loss microwave dielectric ceramic Mg 2-x Ga x Si 1-x Al x O4.
[0025] Figure 2 is (1-y)Mg in Comparative Examples 4 to 5 and Examples 5 to 9 1.99 Ga 0.01 Si 0.99 Al 0.01 The microwave dielectric properties of O4-yCaTiO3 vary with the component y. Obviously, when 9wt%≤y≤13wt%, the addition of CaTiO3 can improve the temperature stability of the ceramic, and has good application value in application scenarios with large temperature changes. DETAILED DESCRIPTION
[0026] The above-mentioned purpose of the present invention is achieved by the following technical methods:
[0027] A low-loss temperature-stable forsterite type microwave dielectric ceramic material and a preparation method thereof, the preparation method comprising the following steps:
[0028] (1) The raw materials MgO, Ga2O3, Al2O3, SiO2 and CaTiO3 used are pretreated; the MgO used needs to be calcined at 900°C for 2 hours before weighing to decompose the basic magnesium carbonate (Mg(OH)2CO3) formed due to water absorption. The Ga2O3, Al2O3, SiO2 and CaTiO3 used need to be placed in an oven at 80°C for 24 hours before weighing to remove the adsorbed water.
[0029] (2) MgO, Ga2O3, SiO2, and Al2O3 were weighed according to the molar ratio of Mg:Ga:Si:Al being 2-x:x:1-x:x, where 0<x≤0.02mol, and the mixed mixture was placed in a ball mill filled with ZrO2 balls. Anhydrous ethanol was added to the ball mill for one ball milling. The ball milling time was 24h and the rotation speed was 220r / min.
[0030] (3) drying, grinding, sieving, and then pre-calcining the powder after the first ball milling; the drying temperature is 80° C., the drying time is 24 h, the sieving uses a 100-mesh standard sieve, the pre-calcining conditions are 1150° C. for 3 h, the heating rate is 4° C. / min, the temperature is kept at 1150° C. for 3 h, and then cooled to room temperature with the furnace.
[0031] (4) Grind the pre-sintered powder, weigh and mix with CaTiO3 according to the mass ratio of (1-y):y, where 9%≤y≤13%, place in a ball mill, add ZrO2 balls and anhydrous ethanol, and perform secondary ball milling; the secondary ball milling time is 12 hours, the speed is 220r / min. The drying temperature is 80°C, and the drying time is 24 to 36 hours.
[0032] (5) After drying the powder after the secondary ball milling, a polyvinyl alcohol (PVA) aqueous solution with a concentration of 10wt% is used as a binder, and PVA accounting for about 10wt% of the powder mass is added, and a standard sieve of 60 mesh is used for screening. A steel mold with a diameter of 12mm is used, and a pressure of 100-150MPa is used to press it into a cylindrical body with a height of 4-6mm and a diameter of 12mm, and then sintering is performed. The specific steps are: first, the temperature is increased to 650℃ at a rate of 2℃ / min to debind for 3h, and then the temperature is increased to 1250-1400℃ at a rate of 4℃ / min and sintered for 3h, and then the temperature is decreased to 800℃ at a rate of 2℃ / min and then decreased to room temperature to obtain the microwave dielectric ceramic.
[0033] Example 1
[0034] This embodiment provides a low dielectric constant and low loss microwave dielectric ceramic material Mg 1.9975 Ga 0.0025 Si 0.997 5Al 0.0025 Preparation method of O4:
[0035] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.9975:0.00125:0.9975:0.00125. Pretreat the raw materials before mixing. MgO needs to be calcined at 900°C for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80°C for 24h before weighing to ensure the accuracy of the ratio.
[0036] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 170 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0037] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1200°C at a heating rate of 5°C / min. After being kept at this temperature for 4 h, the temperature was cooled to room temperature along with the furnace.
[0038] (4) The pre-sintered raw materials were transferred to a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the raw materials were placed in a ball mill for 12 hours at a speed of 170 r / min. The slurry after the second ball milling was dried at 80°C for 24 hours.
[0039] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then 10 wt % PVA solution was added as a binder. After being fully mixed and ground, the powder was passed through a 40-mesh standard sieve.
[0040] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 80 MPa to 100 MPa.
[0041] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1500°C at a rate of 5°C / min and kept at that temperature for 4 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0042] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 6.7, a quality factor of 207200 GHz, and a resonant frequency temperature coefficient of -46 ppm / °C.
[0043] Example 2
[0044] This embodiment provides a low dielectric constant and low loss microwave dielectric ceramic material Mg 1.995 Ga 0.005 Si 0.995 Al 0.005 Preparation method of O4:
[0045] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.995:0.0025:0.995:0.0025. Pretreat the raw materials before mixing. MgO needs to be calcined at 900°C for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80°C for 24h before weighing to ensure the accuracy of the ratio.
[0046] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 170 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0047] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1200°C at a heating rate of 5°C / min. After being kept at this temperature for 4 h, the temperature was cooled to room temperature along with the furnace.
[0048] (4) The pre-sintered raw materials were transferred to a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the raw materials were placed in a ball mill for 12 hours at a speed of 170 r / min. The slurry after the second ball milling was dried at 80°C for 24 hours.
[0049] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then 10 wt % PVA solution was added as a binder. After being fully mixed and ground, the powder was passed through a 40-mesh standard sieve.
[0050] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 80 MPa to 100 MPa.
[0051] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1450°C at a rate of 5°C / min and kept at that temperature for 4 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain microwave dielectric ceramics.
[0052] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 6.73, a quality factor of 215600 GHz, and a resonant frequency temperature coefficient of -48 ppm / °C.
[0053] Example 3
[0054] This embodiment provides a low dielectric constant and low loss microwave dielectric ceramic material Mg 1.99 Ga 0.01 Si 0.99 Al 0.01Preparation method of O4:
[0055] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.99:0.005:0.99:0.005. Pretreat the raw materials before mixing. MgO needs to be calcined at 900°C for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80°C for 24h before weighing to ensure the accuracy of the ratio.
[0056] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 170 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0057] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1200°C at a heating rate of 5°C / min. After being kept at this temperature for 4 h, the temperature was cooled to room temperature along with the furnace.
[0058] (4) The pre-sintered raw materials were transferred to a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the raw materials were placed in a ball mill for 12 hours at a speed of 170 r / min. The slurry after the second ball milling was dried at 80°C for 24 hours.
[0059] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then 10 wt % PVA solution was added as a binder. After being fully mixed and ground, the powder was passed through a 40-mesh standard sieve.
[0060] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 80 MPa to 100 MPa.
[0061] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1450°C at a rate of 5°C / min and kept at that temperature for 4 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain microwave dielectric ceramics.
[0062] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 6.95, a quality factor of 236600 GHz, and a resonant frequency temperature coefficient of -38 ppm / °C.
[0063] Example 4
[0064] This embodiment provides a low dielectric constant and low loss microwave dielectric ceramic material Mg 1.985 Ga 0.015Si 0.985 Al 0.015 Preparation method of O4:
[0065] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.985:0.015:0.985:0.015. Pretreat the raw materials before mixing. MgO needs to be calcined at 900°C for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80°C for 24h before weighing to ensure the accuracy of the ratio.
[0066] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 170 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0067] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1200°C at a heating rate of 5°C / min. After being kept at this temperature for 4 h, the temperature was cooled to room temperature along with the furnace.
[0068] (4) The pre-sintered raw materials were transferred to a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the raw materials were placed in a ball mill for 12 hours at a speed of 170 r / min. The slurry after the second ball milling was dried at 80°C for 24 hours.
[0069] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then 10 wt % PVA solution was added as a binder. After being fully mixed and ground, the powder was passed through a 40-mesh standard sieve.
[0070] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 80 MPa to 100 MPa.
[0071] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1450°C at a rate of 5°C / min and kept at that temperature for 4 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain microwave dielectric ceramics.
[0072] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 6.92, a quality factor of 216200 GHz, and a resonant frequency temperature coefficient of -42 ppm / °C.
[0073] Example 5
[0074] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material 91wt% Mg 1.99 Ga 0.01 Si 0.99 Al 0.01 Preparation method of O4-9wt%CaTiO3:
[0075] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.99:0.01:0.99:0.01. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0076] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0077] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0078] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.91:0.09, mix it and place it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and place it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0079] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then a 10 wt % PVA solution was added as a binder. The powder was fully mixed and ground, and then passed through a 60-mesh standard sieve.
[0080] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0081] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0082] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 8.38, a quality factor of 94500 GHz, and a resonant frequency temperature coefficient of -16.96 ppm / °C.
[0083] Example 6
[0084] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material 90wt% Mg 1.99 Ga 0.01 Si 0.99 Al 0.01 Preparation method of O4-10wt%CaTiO3:
[0085] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.99:0.01:0.99:0.01. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0086] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0087] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0088] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.9:0.1, mix it and place it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and place it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0089] (5) The dried powder was manually ground, passed through a 120-mesh standard sieve, and then 10 wt % PVA solution was added as a binder. After thorough mixing and grinding, the powder was passed through a 60-mesh standard sieve.
[0090] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0091] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0092] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 8.32, a quality factor of 86400 GHz, and a resonant frequency temperature coefficient of -9.55 ppm / °C.
[0093] Example 7
[0094] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material 89wt% Mg 1.99 Ga 0.01 Si 0.99 Al 0.01 Preparation method of O4-11wt%CaTiO3:
[0095] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.99:0.01:0.99:0.01. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0096] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0097] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0098] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.89:0.11, mix it and place it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and place it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0099] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then a 10 wt % PVA solution was added as a binder. The powder was fully mixed and ground, and then passed through a 60-mesh standard sieve.
[0100] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0101] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0102] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 8.55, a quality factor of 72900 GHz, and a resonant frequency temperature coefficient of -2.72 ppm / °C.
[0103] Example 8
[0104] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material 88wt% Mg 1.99 Ga 0.01 Si 0.99 Al 0.01 Preparation method of O4-12wt%CaTiO3:
[0105] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.99:0.01:0.99:0.01. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0106] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0107] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0108] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.88:0.12, mix it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and mill it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0109] (5) The dried powder was manually ground and passed through a 100-mesh standard sieve, 10 wt % PVA solution was added as a binder, and the mixture was thoroughly mixed and ground and passed through a 60-mesh standard sieve.
[0110] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0111] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0112] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 9.08, a quality factor of 51600 GHz, and a resonant frequency temperature coefficient of 5.71 ppm / °C.
[0113] Example 9
[0114] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material 87wt% Mg 1.99 Ga 0.01 Si 0.99 Al 0.01 Preparation method of O4-13wt%CaTiO3:
[0115] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.99:0.01:0.99:0.01. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0116] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0117] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0118] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.87:0.13, mix it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and put it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0119] (5) The dried powder was manually ground and passed through a 100-mesh standard sieve, 10 wt % PVA solution was added as a binder, and the mixture was thoroughly mixed and ground and passed through a 60-mesh standard sieve.
[0120] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0121] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0122] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 9.52, a quality factor of 39000 GHz, and a resonant frequency temperature coefficient of 12.59 ppm / °C.
[0123] Example 10
[0124] This embodiment provides a method for preparing a low dielectric constant, low loss microwave dielectric ceramic material 89wt% Mg2SiO4-11wt% CaTiO3:
[0125] (1) Use MgO (99.99%) and SiO2 (99.5%) as raw materials, and weigh MgO and SiO2 according to the stoichiometric ratio of Mg:Si at a molar ratio of 2:1. Pre-treat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and SiO2 needs to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0126] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0127] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0128] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.89:0.11, mix it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and mill it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0129] (5) The dried powder was manually ground and passed through a 100-mesh standard sieve, 10 wt % PVA solution was added as a binder, and the mixture was thoroughly mixed and ground and passed through a 60-mesh standard sieve.
[0130] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0131] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0132] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 8.35, a quality factor of 59800 GHz, and a resonant frequency temperature coefficient of -8.46 ppm / °C.
[0133] Embodiment 11
[0134] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material 89wt% Mg 1.995 Ga 0.005 Si 0.995 Al 0.005 Preparation method of O4-11wt%CaTiO3:
[0135] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.995:0.005:0.995:0.005. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0136] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0137] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0138] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.89:0.11, mix it and place it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and place it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0139] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then a 10 wt % PVA solution was added as a binder. The powder was fully mixed and ground, and then passed through a 60-mesh standard sieve.
[0140] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0141] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0142] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 8.58, a quality factor of 62300 GHz, and a resonant frequency temperature coefficient of -4.98 ppm / °C.
[0143] Example 12
[0144] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material 89wt% Mg 1.98 Ga 0.02 Si 0.98 Al 0.02 Preparation method of O4-11wt%CaTiO3:
[0145] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.98:0.02:0.98:0.02. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0146] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0147] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0148] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.89:0.11, mix it and place it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and place it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0149] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then a 10 wt % PVA solution was added as a binder. The powder was fully mixed and ground, and then passed through a 60-mesh standard sieve.
[0150] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0151] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0152] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 8.47, a quality factor of 53400 GHz, and a resonant frequency temperature coefficient of -4.24 ppm / °C.
[0153] Comparative Example 1
[0154] This comparative example provides a method for preparing a microwave dielectric ceramic material Mg2SiO4:
[0155] (1) Use MgO (99.99%) and SiO2 (99.5%) as raw materials, and weigh and mix them according to the stoichiometric ratio of MgO:SiO2=2:1. Pre-treat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and SiO2 needs to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0156] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 170 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0157] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 5°C / min. After being kept at this temperature for 4 h, the temperature was cooled to room temperature along with the furnace.
[0158] (4) The pre-sintered raw materials were transferred to a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the raw materials were placed in a ball mill for 12 hours at a speed of 170 r / min. The slurry after the second ball milling was dried at 80°C for 24 hours.
[0159] (5) The dried powder was manually ground and passed through a 100-mesh sieve, 10 wt % PVA solution was added as a binder, and the mixture was thoroughly mixed and ground and passed through a 40-mesh standard sieve.
[0160] (6) About 0.9 g of the granulated raw material is weighed and poured into a steel mold, and molded into a green body with a diameter of 12 mm and a height of about 5 mm under a pressure of 80 MPa to 100 MPa.
[0161] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1450°C at a rate of 5°C / min and kept at that temperature for 4 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain microwave dielectric ceramics.
[0162] The microwave dielectric ceramic material prepared in this comparative example has a dielectric constant of 6.77, a quality factor of 203700GHz, and a resonant frequency temperature coefficient of -54ppm / ℃
[0163] Comparative Example 2
[0164] This comparative example provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.98 Ga 0.02 Si 0.98 Al 0.02 Preparation method of O4:
[0165] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.98:0.02:0.98:0.02. Pretreat the raw materials before mixing. MgO needs to be calcined at 900°C for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80°C for 24h before weighing to ensure the accuracy of the ratio.
[0166] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 170 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0167] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1200°C at a heating rate of 5°C / min. After being kept at this temperature for 4 h, the temperature was cooled to room temperature along with the furnace.
[0168] (4) The pre-sintered raw materials were transferred to a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the raw materials were placed in a ball mill for 12 hours at a speed of 170 r / min. The slurry after the second ball milling was dried at 80°C for 24 hours.
[0169] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then 10 wt % PVA solution was added as a binder. After being fully mixed and ground, the powder was passed through a 40-mesh standard sieve.
[0170] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 80 MPa to 100 MPa.
[0171] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1450°C at a rate of 5°C / min and kept at that temperature for 4 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain microwave dielectric ceramics.
[0172] The microwave dielectric ceramic material prepared in this comparative example has a dielectric constant of 6.9, a quality factor of 175500GHz, and a resonant frequency temperature coefficient of -40ppm / ℃
[0173] Comparative Example 3
[0174] This comparative example provides a low dielectric constant, low loss microwave dielectric ceramic material Mg 1.97 Ga 0.03 Si 0.97 Al 0.03Preparation method of O4:
[0175] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.97:0.03:0.97:0.03. Pretreat the raw materials before mixing. MgO needs to be calcined at 900°C for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80°C for 24h before weighing to ensure the accuracy of the ratio.
[0176] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 170 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0177] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1200°C at a heating rate of 5°C / min. After being kept at this temperature for 4 h, the temperature was cooled to room temperature along with the furnace.
[0178] (4) The pre-sintered raw materials were transferred to a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the raw materials were placed in a ball mill for 12 hours at a speed of 170 r / min. The slurry after the second ball milling was dried at 80°C for 24 hours.
[0179] (5) The dried powder was manually ground, passed through a 100-mesh standard sieve, and then 10 wt % PVA solution was added as a binder. After being fully mixed and ground, the powder was passed through a 40-mesh standard sieve.
[0180] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 80 MPa to 100 MPa.
[0181] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1450°C at a rate of 5°C / min and kept at that temperature for 4 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain microwave dielectric ceramics.
[0182] The microwave dielectric ceramic material prepared in this comparative example has a dielectric constant of 6.82, a quality factor of 112100GHz, and a resonant frequency temperature coefficient of -48ppm / ℃
[0183] Comparative Example 4
[0184] This comparative example provides a low dielectric constant, low loss microwave dielectric ceramic material 93wt% Mg 1.99 Ga0.01 Si 0.99 Al 0.01 Preparation method of O4-7wt%CaTiO3:
[0185] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.99:0.01:0.99:0.01. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0186] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0187] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0188] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.93:0.07, mix it and place it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and place it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0189] (5) The dried powder was manually ground and passed through a 100-mesh standard sieve, 10 wt % PVA solution was added as a binder, and the mixture was thoroughly mixed and ground and passed through a 60-mesh standard sieve.
[0190] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0191] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0192] The microwave dielectric ceramic material prepared in this comparative example has a dielectric constant of 7.99, a quality factor of 96600GHz, and a resonant frequency temperature coefficient of -25.55ppm / ℃
[0193] Comparative Example 5
[0194] This embodiment provides a low dielectric constant, low loss microwave dielectric ceramic material 86wt% Mg 1.99 Ga 0.01 Si 0.99 Al 0.01 Preparation method of O4-14wt%CaTiO3:
[0195] (1) Use MgO (99.99%), Ga2O3 (99.99%), Al2O3 (99.99%), and SiO2 (99.5%) as raw materials, and weigh MgO, Ga2O3, SiO2, and Al2O3 according to the stoichiometric ratio of Mg:Ga:Si:Al of 1.99:0.01:0.99:0.01. Pretreat the raw materials before mixing. MgO needs to be calcined at 900℃ for 2h before weighing, and Ga2O3, Al2O3, and SiO2 need to be dried at 80℃ for 24h before weighing to ensure the accuracy of the ratio.
[0196] (2) The weighed raw materials were transferred into a ball mill, anhydrous ethanol and zirconium dioxide balls were added, and the mixture was ball milled for 24 h at a speed of 220 r / min. After ball milling, the mixture was dried at 80°C for 24 h.
[0197] (3) The dried powder was ground and passed through a 120-mesh standard sieve, and pre-fired at 1150°C at a heating rate of 4°C / min. After being kept at this temperature for 3 h, the temperature was cooled to room temperature along with the furnace.
[0198] (4) Grind the calcined powder, weigh it with CaTiO3 in a mass ratio of 0.86:0.14, mix it and place it in a ball mill, move it to the ball mill, add anhydrous ethanol and zirconium dioxide balls, and place it in a ball mill for 12 hours at a speed of 220 r / min. After the second ball milling, dry the slurry at 80°C for 24 hours.
[0199] (5) The dried powder was manually ground and passed through a 100-mesh standard sieve, 10 wt % PVA solution was added as a binder, and the mixture was thoroughly mixed and ground and passed through a 60-mesh standard sieve.
[0200] (6) About 0.9 g of the granulated raw material is weighed and poured into a mold with an inner diameter of 12 mm. A green body with a height of about 4 mm is formed under a pressure of 100 MPa to 150 MPa.
[0201] (7) The embryo was heated from room temperature to 650°C at a rate of 2°C / min and kept at that temperature for 3 h for debinding, then heated to 1350°C at a rate of 4°C / min and kept at that temperature for 3 h, then cooled to 800°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain a microwave dielectric ceramic.
[0202] The microwave dielectric ceramic material prepared in this embodiment has a dielectric constant of 10.15, a quality factor of 19000 GHz, and a resonant frequency temperature coefficient of 20.22 ppm / °C.
[0203] Figure 1 Mg in Comparative Examples 1 to 3 and Examples 1 to 4 2-x Ga x Si 1-x Al x The Q×f value of O4 at the optimal sintering temperature varies with x; obviously Ga 3+ 、Al 3+ Cooperative substitution occupies part of the Mg in the Mg2SiO4 lattice 2+ and Si 4+ When 0≤x≤0.02mol, an ultra-low loss microwave dielectric ceramic Mg 2-x Ga x Si 1-x Al x O4.
[0204] Figure 2 is (1-y)Mg in Comparative Examples 4 to 5 and Examples 5 to 9 1.99 Ga 0.01 Si 0.99 Al 0.01 The microwave dielectric properties of O4-yCaTiO3 vary with the component y. Obviously, when 9wt%≤y≤13wt%, the addition of CaTiO3 can improve the temperature stability of the ceramic, and has good application value in application scenarios with large temperature changes.
[0205] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, and it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A low-loss temperature-stable olivine-type microwave dielectric ceramic, characterized in that: The chemical formula of the low-loss temperature-stable olivine-type microwave dielectric ceramic is (1-y)Mg 2-x Ga x Si 1-x Al x O4-yCaTiO3, Among them, the range of subscript x is 0<x≤0.01, Mg 2-x Ga x Si 1-x Al x The mass ratio of O4 to CaTiO3 is (1-y):y; the range of y is 9%≤y≤11%; Mg 2-x Ga x Si 1-x Al x O4 is through Ga 3+ , Al 3+ ions replace Mg 2+ and Si 4+ The microwave dielectric ceramic is composed of a phase Mg 2-x Ga x Si 1-x Al x The invention discloses an olivine composite ceramic composed of O4 and CaTiO3. The low-loss temperature-stable olivine microwave dielectric ceramic has a dielectric constant of 8.32 to 8.55, a Q×f of 72900 GHz to 94500 GHz, and a resonant frequency temperature coefficient of -16.96 to -2.72 ppm / °C.
2. The method for preparing a low-loss temperature-stable olivine-type microwave dielectric ceramic according to claim 1, characterized in that: The following steps are involved: (1) Obtaining raw materials MgO, Ga2O3, Al2O3, SiO2, CaTiO 3, Purifying the raw materials MgO, Ga2O3, Al2O3, SiO2 and CaTiO3; (2) weighing raw materials according to the molar ratio of Mg:Ga:Si:Al of 2-x:x:1-x:x, mixing and placing in a ball mill filled with ZrO2 balls, adding 4 / 5 of anhydrous ethanol to the ball mill for a first ball milling to obtain a powder after a first ball milling; wherein the range of x is 0<x≤0.01; (3) drying, grinding, sieving, and then pre-calcining the powder after the first ball milling; (4) Grind the pre-burned powder and then press Mg 2-x Ga x Si 1-x Al x The mass ratio of O4 to CaTiO3 is (1-y):y; CaTiO3 is added, the mixture is placed in a ball mill, ZrO2 balls and anhydrous ethanol are added, and secondary ball milling is performed to obtain a powder after secondary ball milling; wherein the range of y is: 9%≤y≤11%; (5) the powder after secondary ball milling is dried, and then the powder is screened for the first time, granulated, screened for the second time, pressed into tablets, and finally sintered to obtain the microwave dielectric ceramic.
3. The preparation method according to claim 2, characterized in that: The specific steps of the purification treatment in step (1) are: calcining the MgO at 900°C for 2 hours to decompose the basic magnesium carbonate Mg(OH)2CO3 formed due to water absorption; and drying the Ga2O3, Al2O3, SiO2 and CaTiO3 at 80°C for 24 hours to remove moisture.
4. The preparation method according to claim 3, characterized in that: The specific conditions of the first ball milling in step (2) are: a rotation speed of 220 r / min and a time of 12-24 h.
5. The preparation method according to claim 4, characterized in that: In the step (3), the drying temperature is 80°C, the drying time is 24 hours, the sieving uses a 100-mesh standard sieve, the pre-burning condition is 1150°C, the heating rate is 4°C / min, the temperature is kept at 1150°C for 4 hours and then cooled to room temperature with the furnace.
6. The preparation method according to claim 5, characterized in that: The specific conditions of the secondary ball milling in step (4) are: a rotation speed of 220 r / min and a time of 12-24 h.
7. The preparation method according to claim 6, characterized in that: In the step (5), the drying condition is 80° C. for 24 to 36 hours, the first sieving uses a 100-mesh standard sieve, and then polyvinyl alcohol (PVA) with a powder mass of 10 wt% and a concentration of 10 wt% is added as a binder for granulation, and the second sieving uses a 60-mesh standard sieve; the tabletting uses 0.9 g to 1.1 g of powder in a steel mold with a diameter of 12 mm, and is pressed into a cylindrical blank with a height of 4 to 6 mm and a diameter of 12 mm under a pressure of 150 MPa.
8. The preparation method according to claim 7, characterized in that: In the step (5), the sintering includes: first heating to 650°C at a rate of 2°C / min for debinding for 3 hours, then heating to 1250-1400°C at a rate of 4°C / min for sintering for 3 hours, and finally cooling to 800°C at a rate of 2°C / min and then cooling to room temperature with the furnace.
Citation Information
Patent Citations
A low-temperature co-fired ceramic material and a preparing method thereof
CN106032318A
Low-dielectric constant high-quality microwave ceramic medium and production process thereof
CN101429009A
Low dielectric constant microwave dielectric ceramic with zero frequency temperature coefficient and ultra-low loss and preparation method of ceramic
CN107805067A
Mg2-xMxSiO4CaTiO3 composite microwave dielectric ceramic and preparation method thereof
CN111995383A